2011
DOI: 10.1016/j.addbeh.2010.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and drug use among patients presenting to an inner-city emergency department: A latent class analysis

Abstract: The inner city Emergency Department (ED) provides a window of opportunity for screening for alcohol and other drug misuse and substance use disorders (SUDs), in order to facilitate linkage for individuals who are in need of services targeting such issues. The majority of prior work in this area has focused on alcohol use. This study used latent class analyses to characterize substance use/SUDs among adults presenting to the ED for medical complaints or injuries. Participants (n=14,557; 77% participation; 45% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 57 publications
3
37
0
2
Order By: Relevance
“…For example, tobacco smoking may be a convenient marker for other substance use problems, as patients often easily acknowledge smoking. Given the mixed results for the association of triage level with ATOD problems, our data also support expanding SBI to include non-trauma patients and non-trauma EDs, consistent with results reported by Blow et al (2011) who found that poly-drug users were more likely to present with medical problems than injuries.…”
Section: Discussionsupporting
confidence: 90%
“…For example, tobacco smoking may be a convenient marker for other substance use problems, as patients often easily acknowledge smoking. Given the mixed results for the association of triage level with ATOD problems, our data also support expanding SBI to include non-trauma patients and non-trauma EDs, consistent with results reported by Blow et al (2011) who found that poly-drug users were more likely to present with medical problems than injuries.…”
Section: Discussionsupporting
confidence: 90%
“…Prior analysis of the sample has shown that there was frequent marijuana use across whole sample (Blow et al, 2011) and another research has shown that acute marijuana intoxication can decrease aggression . Additional research is needed to better understand both social contextual factors and substance use problems as they relate to partner and non-partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…Much research on the prevalence of MSU has been conducted in clinical samples (Blow et al, 2011;Byqvist, 1999;Martin, Kaczynski, Maisto, & Tarter, 1996), university samples (Barrett, Darredeau, & Pihl, 2006;Martin, Clifford, & Clapper, 1992) or youth samples (Collins et al, 1998;Merrill, Kleber, Shwartz, Liu, & Lewis, 1999). Fewer studies have assessed MSU in the general population.…”
Section: Introductionmentioning
confidence: 98%